2013
DOI: 10.1155/2013/406927
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Preclinical Rheumatoid Arthritis-Associated Interstitial Lung Disease

Abstract: Objective. Interstitial lung disease (ILD) is a common extra-articular manifestation of rheumatoid arthritis (RA) and a significant cause of morbidity and mortality. The objective of this study was to define high-resolution chest CT (HRCT) and pulmonary function test (PFT) abnormalities capable of identifying asymptomatic, preclinical forms of RA-ILD that may represent precursors to more severe fibrotic lung disease. Methods. We analyzed chest HRCTs in consecutively enrolled RA patients and subsequently classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 13 publications
5
64
2
5
Order By: Relevance
“…RA-related interstitial lung disease (RA-ILD) is increasingly recognized and is clinically significant in 5-10 % of RA patients [4,5]. Using high-resolution computed tomography (HRCT) scanning, the estimated prevalence of ILD and airway disease among RA patients was 19-56 % [6][7][8] and 25-30 % [9-11], respectively. In spite of this Electronic supplementary material The online version of this article (doi:10.1007/s00408-016-9916-x) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…RA-related interstitial lung disease (RA-ILD) is increasingly recognized and is clinically significant in 5-10 % of RA patients [4,5]. Using high-resolution computed tomography (HRCT) scanning, the estimated prevalence of ILD and airway disease among RA patients was 19-56 % [6][7][8] and 25-30 % [9-11], respectively. In spite of this Electronic supplementary material The online version of this article (doi:10.1007/s00408-016-9916-x) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…They found no significant correlation between HRCT findings and disease activity, RF positivity, PFT results and disease duration. In the study of Chen et al [24] the overall prevalence of radiologically defined RA-ILD in RA patients was high (61%) though the frequency of clinically evident ILD was only Table 4 Comparison of demographic features, disease activity, immune profile and PFT between RA patients with and without ILD. 6%.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms complained of by RA patients with ILD include various degrees of exertional dyspnoea and coughing that require further investigation with pulmonary function tests (PFT), chest X-ray and eventually HRCT. However, the diagnosis of RA-ILD may often be incidental as 30-90% of patients with RA-ILD, according to different studies, may have no or very mild respiratory symptoms (10,11). The burden of clinically manifest ILD on RA prognosis is critical, with an overall median survival ranging between 2.6 and 8.1 years after diagnosis.…”
Section: Reviewmentioning
confidence: 99%
“…Moreover, a recent meta-analysis reported that RA-ILD is not significantly associated with ACPA in a specific ethnic group, namely a subset of Asian RA patients (23). Since RF/ACPA positivity is associated with more severe articular disease, the fact that joint disease severity appears to be linked to RA-ILD is easy to explain (10,13).…”
Section: Reviewmentioning
confidence: 99%